Non-contrast-enhanced MRI of the pulmonary blood volume using two-compartment-modeled T1-relaxation - Gaass, Thomas; Dinkel, Julien; Bauman, Grzegorz; Zaiss, Moritz; Hintze, Christian; Haase, Axel; Laun, Frederik Bernd (Journal of Magnetic Resonance Imaging, 2012)
Purpose: To introduce a novel technique, based on a two-compartment model and nonselective inversion recovery (TCIR) for the non-contrast-enhanced evaluation of the fractional pulmonary blood volume (fPBV). Materials and Methods: Ten healthy volunteers and one patient with focal lung destruction underwent examination with conventional magnetic resonance imaging (MRI) and TCIR. The reproducibility of TCIR was evaluated statistically, analyzing three consecutive measurement series. In order to evaluate the sensitivity of TCIR, the influence of gravitation on fPBV values along the anterior-posterior direction was assessed. Therefore, two transverse parameter maps of each volunteer in supine and prone position were acquired and analyzed. A comparison of patient images from TCIR-MRI, dynamic contrast-enhanced (DCE) MRI, and contrast-enhanced computed tomography (CT) was performed visually. Results: The statistical evaluation showed significant similarity within the volunteer group, proving reproducibility. The detected slope of the fPBV values in anterior-posterior direction for both supine and prone position demonstrated the sensitivity of TCIR to the gravitational effect on the pulmonary blood distribution. The comparison between CT, DCE-, and TCIR-MRI patient datasets showed high similarity in dimension and location of the pathological part of the lung parenchyma. Conclusion: The introduced TCIR-technique is able to provide reproducible maps of the fPBV without the application of intravenous contrast media. Copyright © 2012 Wiley Periodicals, Inc.
CRIS-Team Scopus Importer:2022-08-05
Keywords: lung MRI; non-contrast-enhanced; pulmonary; pulmonary perfusion imaging; two compartment